Manajemen Risiko Likuiditas : Jaminan Keberlanjutan dan Ketahanan Bank Syariah di Era Krisis Moneter - Risma Wati; Muhammad Iqbal Fasa (MAMEN: Jurnal Manajemen, 2024)
Sharia banking risk management is a process of controlling risks arising from Shariah-compliant activities. In this regard, liquidity risk management becomes a crucial factor as it has the potential to impact the sustainability and resilience of Sharia banks. Adequate liquidity allows Sharia banks to meet their financial obligations, maintain customer confidence, and operate stably, even in volatile market conditions. In a competitive landscape, Islamic banks need to understand, control, and regularly monitor the risks they face. This is essential to ensure they can manage liquidity effectively and avoid potential financial losses. This paper examines the causes of liquidity risk in Islamic banks, which are influenced by the Shariah principle prohibiting interest in business transactions. This prohibition of interest creates unique challenges in liquidity management, as Sharia banks must seek alternative funding sources and carefully manage assets. Although Islamic banks have shown resilience during crises, this study highlights their challenges in maintaining liquidity. These challenges include fluctuations in fund flows, regulatory changes, and competition from conventional banks. This paper also examines the main causes of liquidity risk in Islamic banks and concludes with managerial and policy recommendations to address liquidity risk management issues to prevent potential future financial crises. These recommendations include developing diversified funding strategies, enhancing transparency and accountability, and collaborating with other Sharia financial institutions. By effectively managing liquidity risk, Sharia banks can continue to grow and make positive contributions to the economy.